Generalized Anxiety Disorder Tokoh Akiko dalam Drama Okaasan Musume wo Yamete Ii Desuka Karya Tomochika Kasaura - Tiara Maharani, Ayu Bintang (Humanis, 2018)
The title of this research is “The Generalized Anxiety Disorder of Akiko Figure in Okaasan Musume wo Yamete Ii Desuka Drama by Tomochika Kasaura”. This research aims to provide information about characteristics, factors, and effort s of Akiko Hayase figure to tackle Generalized Anxiety Disorder ( GAD ) . The method s used are descriptive analysis method and informal method. The theor i es used in analyzed are psychology literature theory by Wellek and Warren (2016), generalized anxiety disorder theory (DSM-IV-TR) by Davison (2014), psychoanalysis theory by Freud (2016), and semiotic theory by Danesi (2011). Based on the analysis result, there were five characteristics of GAD found in Akiko Hayase figure such as, 1) experiencing anxiety or worry to excessive; 2) feeling tired to easily; 3) irritability and offended; 4) nervous or have an pressure; 5) performing deviant acts. The GAD in Akiko Hayase figure was cause by psychoanalysis factors such as, 1) Feeling fear of being left by a loved one; 2) unfulfilled desires; 3) an memory in past failures. The behaviour-cognitive factors is rejection the existence of Akiko by Mizuki. The effort of Akiko Hayase figure to tackle GAD consist of internal effort such as, 1) trying to establish a harmonious relationship; 2) trying to have a skill. As for external effort such as, 1) trying to give calmness for Akiko; 2) trying to invite Akiko for start a new life.